Determinants of medication non-adherence among pulmonary tuberculosis patients: A cross-sectional secondary data analysis - Naila Farsya; Evi Susanti Sinaga (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Pulmonary tuberculosis is an infectious disease that remains as a major public health problem in Indonesia. Successful tuberculosis treatment largely depends on patients’ adherence to regular and continuous medication intake. Medication adherence behavior can be classified into adherence and non-adherence, with the medication non-adherence behavior increasing the risk of treatment failure, drug resistance, disease relapse, and ongoing transmission. This behavior is determined by a range of factors operating at the individual, social, and health system levels. Purpose: To analyze the determinants associated with medication non-adherence behavior among pulmonary tuberculosis patients based on data from the 2023 Indonesian Health Survey. Method: A cross-sectional observational study was conducted using secondary data from the 2023 Indonesian Health Survey, including 2,435 respondents, all of whom were pulmonary tuberculosis patients recorded in the SKI 2023 dataset. Independent variables consist of predisposing factors (age, gender, education, employment status, place of residence, perception of being cured, use of traditional medicine, intolerance to drug side effects, and boredom or reluctance to take medication regularly), enabling factors (limited availability of medication), and reinforcing factors (presence of a treatment supervisor). Medication non-adherence behavior was the dependent variable in this study and the bivariate analysis was performed using chi-square tests, with statistical significance set at p < 0.05. Results: The findings showed significant associations between medication non-adherence behavior and several predisposing, enabling, and reinforcing factors (p < 0.05). Predisposing factors significantly associated with irregular medication intake including age, education, employment status, place of residence, perception of being cured, use of traditional medicine, intolerance to drug side effects, and boredom or reluctance to take medication regularly. Enabling factors, particularly limited availability of anti-tuberculosis medication at health facilities, were also significantly associated with irregular medication-taking behavior. In addition, reinforcing factors, namely the absence of a treatment supervisor, showed a significant association with irregular medication taking behavior. Conclusion: Medication non-adherence behavior among pulmonary tuberculosis patients is influenced by predisposing, enabling, and reinforcing factors. Improving treatment adherence requires comprehensive strategies, including strengthened patient education, improved access and availability of tuberculosis services, and strengthened treatment supervision through the presence of a treatment supervisor.